Broad-band SiGe MMICs for phased-array radar applications. - Tayrani, R. (IEEE Journal of solid state circuits)
This paper reports the performances of several broad-band monolithic SiGe monolithic microwave integrated circuits (MMICs) suitable for phased-array radar applications. The amplitude and phase control MMIC designs are based on an optimized SiGe p-i-n diode offered by the IBM 5HP SiGe foundry process. Utilizing this diode, several control circuitries including a broad-band (1-20-GHz) monolithic single-pole double-throw switch, a five-port transfer switch, a 6-bit phase shifter, and a 5-bit attenuator, all operating over 7-11 GHz, are designed. Also, the design and performance of an SiGe heterojunction bipolar transistor variable-gain cascode amplifier that combines the functionality of an amplifier and an attenuator into one MMIC is described.